(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the importance of language in artistic works, highlighting the word as the main element for exchanging ideas and creating dreams and goals. The effectiveness of language in artistic works is emphasized, particularly through the skillful use of language units like similes. Simile, a figure of speech based on comparing two things or events to highlight their similarities, is described as a powerful tool for creating vivid and exaggerated descriptions in artistic imagery. Simile is considered one of the oldest and most widely used figurative devices, relying on common characteristics between objects or phenomena being compared.